penerapan green architecture pada perancangan sekolah tinggi meteorologi klimatologi dan geofisika di kota tangerang - Ferian Nur Seloardi; Anggraeni Dyah Sulistiowati; Sri Kurniasih (MAESTRO, 2020)
College is a university which organizes academic education and can also organize vocational education within a certain group of Sciences and Technology and if it meets the requirements, a high school can certainly also hold professional education. Higher education is a continuation of secondary education held to prepare students to become members of the community who have academic and professional abilities that can apply, develop and create science, technology and arts (Law 2 of 1989, article 16, paragraph (1)). In the Tri Dharma of Higher Education, it was mentioned that related to the implementation of three main things namely teaching, research and community service. High school that includes learning about the science of Meteorology, Climatology and Geophysics in order to realize students who have human resources in the field of meteorology who are competitively competitive and provide added value through education and training. Disseminating knowledge in the field of climatology and striving for applications to improve the welfare of society and enrich national culture. Able to observe geophysical elements. has competence according to the department. Green building is a green building with building plans to make life better and meet the needs of the next generation. Especially those related to nature conservation, health, and also social. Green building can be interpreted as sustainable, earthfriendly (environmentally friendly), and high performance building (buildings with very good performance). Green architecture optimizes part of its land for green space, green building is a re-interpretation of the socio-cultural community to nature and shelter life. With the application of green architecture in the design of climatology and geophysics meteorology high schools in the city of Tangerang, it is expected to be known by the community inside and outside the region for the realization of buildings that can provide a place for prospective cadets who are competent in their fields and to explore air quality and power. And also the surrounding community who want to learn about meteorology, climatology, geophysics. As well as having a high appeal because of the realization of a green building.